Pengaruh Fitur dan Citra Merek terhadap Keputusan Pembelian Iphone yang Dimoderasi Gaya Hidup Konsumen di Kabupaten Takalar - Meliska, Riska; Effendi, Ahmad (Study of Scientific and Behavioral Management, 2024)
This research aims to determine the influence of features and brand image on iPhone purchasing decisions which are moderated by consumer lifestyle in TakalarRegency. This research uses primary data and secondary data, the sampling technique in this research uses a non-probability sampling technique using the Hair formula, so the total sample in this research is 120 respondents. This type of research is associative research using a quantitative approach, the data analysis technique in this research is using Structural Equation Modeling (SEM) using the help of SmartPLS version 4.0 for Windows, which is directed at answering the problem formulation or hypothesis that has been formulated in this research and is directed to test the relationship between the feature variable, brand image, and lifestyle-moderated purchasing decisions. The results of this research show that the feature variable has a positive and significant influence on iPhone purchasing decisions, brand image has a positive and significant influence on iPhone purchasing decisions, lifestyle moderates the influence of features on iPhone purchasing decisions, lifestyle moderates the influence of brand image on iPhone purchasing decisions.